2014
DOI: 10.1042/bst20140099
|View full text |Cite
|
Sign up to set email alerts
|

PolyQ-mediated regulation of mRNA granules assembly

Abstract: RNA granules have been observed in different organisms, cell types and under different conditions, and their formation is crucial for the mRNA life cycle. However, very little is known about the molecular mechanisms governing their assembly and disassembly. The aggregation-prone LSCRs (low-sequence-complexity regions), and in particular, the polyQ/N-rich regions, have been extensively studied under pathological conditions due to their role in neurodegenerative diseases. In the present review, we discuss recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Such repeats are present in many regulatory RNA-binding proteins (68), including Bicoid and GIGYF2. These and other low-complexity regions have been implicated in protein aggregation, and in formation of hydrogels and RNA-protein granules (81). EIF4E1 is found in starvation granules (82) (http://tryptag.org/?query=EIF4E1), but it is distributed throughout the cytosol and nucleus under normal conditions (55).…”
Section: Discussionmentioning
confidence: 99%
“…Such repeats are present in many regulatory RNA-binding proteins (68), including Bicoid and GIGYF2. These and other low-complexity regions have been implicated in protein aggregation, and in formation of hydrogels and RNA-protein granules (81). EIF4E1 is found in starvation granules (82) (http://tryptag.org/?query=EIF4E1), but it is distributed throughout the cytosol and nucleus under normal conditions (55).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, polyQs were also found to be enriched in TFs in plants 26 . Besides that, polyQ-containing proteins are proposed to act as key factors for the formation of RNA granules, which are ribonucleoprotein particles that mediate mRNA compartmentalisation 27 . Generally, the dynamic formation of subcellular structures could be necessary for a changing composition of the assemblies in dependence of their functional status 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we found that PLT3, in contrast to PLT1 and PLT2, has polyQ containing PrDs in its aa sequence that are necessary for the localisation to NBs and for complex-formation with WOX5. Proteins containing polyQ-stretches or PrDs are often involved in RNA binding, RNA processing and/or RNA compartmentalisation 27,35,3841 and indeed, the PLT3 NBs co-localise with RNA. Just as PLT3, FLOWERING CONTROL LOCUS A (FCA) is a PrD-containing protein 30 that localises to subnuclear structures 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Such repeats are present in many regulatory RNA-binding proteins, both from trypanosomes ( 68 ), and other species (for example, they are found in Bicoid and GIGYF2). These and other low complexity regions have been implicated in protein aggregation and in formation of hydrogels and RNA–protein granules ( 85 ). EIF4E1 is found in starvation granules ( 78 ) ( http://tryptag.org/?query=EIF4E1 ), but it is distributed throughout the cytosol and nucleus under normal conditions ( 55 ).…”
Section: Discussionmentioning
confidence: 99%